Brucella meningoencephalitis associated with cerebrospinal fluid shunt in a child: case report. - Chowdhary, U.M.; Twum-Danso, K. (PubMed, 1991)
Brucella meningoencephalitis is rare in young children. We describe a patient who developed Brucella meningoencephalitis at the age of 20 months while he had a ventriculoperitoneal shunt in situ for treatment of hydrocephalus. This patient was treated with streptomycin and rifampicin. The shunt was left in situ, and all the clinical and laboratory test abnormalities subsided with this management. We propose that in a patient with Brucella meningoencephalitis, the cerebrospinal fluid shunt system can be left in situ and treatment with appropriate combination of antibiotics should prove to be successful.